2011
DOI: 10.1007/s12311-011-0302-1
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje Cell-Specific Ablation of CaV2.1 Channels is Sufficient to Cause Cerebellar Ataxia in Mice

Abstract: The Cacna1a gene encodes the α1A subunit of voltage-gated CaV2.1 Ca2+ channels that are involved in neurotransmission at central synapses. CaV2.1-α1-knockout (α1KO) mice, which lack CaV2.1 channels in all neurons, have a very severe phenotype of cerebellar ataxia and dystonia, and usually die around postnatal day 20. This early lethality, combined with the wide expression of CaV2.1 channels throughout the cerebellar cortex and nuclei, prohibited determination of the contribution of particular cerebellar cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…4 A, D). The reduced cerebellar size and normal dendritic branching are consistent with another line of PC-specific Ca v 2.1 KO mice, Cacna1a purk(Ϫ/Ϫ) (Mark et al, 2011;Todorov et al, 2011) and global Ca v 2.1 KO mice (Miyazaki et al, 2004). The surface of the somata and proximal dendrites was smooth in control mice ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…4 A, D). The reduced cerebellar size and normal dendritic branching are consistent with another line of PC-specific Ca v 2.1 KO mice, Cacna1a purk(Ϫ/Ϫ) (Mark et al, 2011;Todorov et al, 2011) and global Ca v 2.1 KO mice (Miyazaki et al, 2004). The surface of the somata and proximal dendrites was smooth in control mice ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…We therefore exploited this genotype/phenotype relationship to determine if abnormal PCs were the major determinants of the ataxia associated with the EA2 allele. We have demonstrated that selective elimination of Ca V 2.1 channels within PCs causes ataxia (Todorov et al, 2012) by breeding the L7-Cre transgene, which expresses Cre recombinase in postnatal PCs, onto the floxed Cacna1a mouse strain (flox/flox). Therefore, we used a conditional approach to isolate the ataxia-causing genotype to PCs by breeding the L7-Cre transgene onto EA2/flox mice, creating mice that expressed only the EA2 allele in PCs, but in all other cells, the mice were heterozygous with one normoactive allele and one EA2 allele (EA2/flox; L7-Cre/-).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PCs are the sole output neurons of the cerebellar cortex and PC-specific lesions induce ataxia in humans and animal models (Holmes, 1917, Diener and Dichgans, 1992, Feddersen et al, 1992). Indeed, selective elimination of Ca V 2.1 channels from PCs causes a severe and chronic motor syndrome in mice that includes ataxia (Mark et al, 2011, Todorov et al, 2012). In other spontaneous mouse mutants with point mutations within Cacna1a that lead to moderately hypoconductive Ca V 2.1 channels, the motor dysfunction is somewhat less severe with both chronic and episodic components (Wakamori et al, 1998, Kodama et al, 2006, Shirley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to previously reported protocol (Todorov et al, 2012), the samples were processed by fixation with 4% paraformaldehyde (PFA), dehydration with series of ethanol solution, infiltration and embedding in paraffin. The 5-mm-thick sections of the cerebellum were cut and subsequently processed with H&E staining.…”
Section: Neuropathological Examinationmentioning
confidence: 99%